Strategi Dakwah Bil-Lisan bagi Masyarakat Pedesaan: Studi pada Pengajian Rutin Mushola An-Nur Bakalan Karangpandan - Vian Widiyanto; Joko Sarjono; Agus Fatuh Widoyo (Pawarta: Journal of Communication and Da'wah, 2024)
To achieve happiness in this world and the hereafter, da'wah is an obligation for every Muslim. Islam provides da'wah activists with various methods that they can use according to the circumstances they face during da'wah to realize da'wah work. Da'wah bi al-bahasa is the most important and most effective da'wah method. effective. Descriptive qualitative methods and phenomenological-naturalistic approaches were used in this study. Data collection was done through interviews, observations, and documentation. Data analysis used data preparation, verification, and reduction. The results of the study explain that the An-Nur Mosque in Bakalan Hamlet, Harjosari Village, holds Dakwah Bil Lisan activities led by a Ustad every Friday night after the Maghrib prayer , starting with the reading of the Yasin Letter of the Qur'an, then continuing with the reading of Tahlil, namely the reading of Tasbih, Tahmid, Takbir, Istighfar, and finally prayer. Continued until Isha time filled with lectures with religious strengthening material, the Taklimul Muta'alim Book and also the Aqidatul awam book. Second , this activity is carried out using the Mauidzah Khasanah Method with the help of Qaulan Ma'rufa (kind words), Qaulan Layyina (gentle words), and Qaulan Baligha (words that leave an impression on the heart or soul).